Transferring Knowledge on Patient-Centered Care through the Establishment of an International Network - Lages, Nadine; Scholl, Isabelle; Quezada, Constanza; Hahlweg, Pola; Zeh, Stefan; Dois, Angelina; Bravo, Paulina; Härter, Martin (Das Gesundheitswesen)
Background: Patient-centered care (PCC) is a key principle of high-quality health care. Recently, PCC has become increasingly relevant in many countries. In 2006, Chile declared PCC as a fundamental pillar of its health care system. However, PCC im-plementation in the Chilean healthcare system still lags. Some factors contributing to this are 1) the complexity of the concept, 2) the interdependence between healthcare activities and policy regulations, and 3) the need for a cultural change in health politics and care. This paper shares experiences of how we have tried to address some of these challenges by establishing an international network for PCC. Methods: As part of a collaborative project between researchers and clinicians based in Chile and Germany, we have established the International Network for Patient-Centered Care (PCC NET). The network offered knowledge exchange and trainings through different means. Results: Knowledge exchange was addressed by developing and launching a website that serves as a platform to share knowledge. Furthermore, a series of online semi-nars on PCC was organized, each conducted by an international expert in the field. In January 2023, several face-to-face workshops were developed and held in Chile. In total, 51 participants have attended the workshops. They were either health profes-sionals responsible for implementing PCC in the country, working for the Ministry of Health or in primary care in Chile. We evaluated the workshops by assessing the par-ticipants' reactions via surveys, and the participants rated the workshops positively. In January 2024, the first Latin American Conference on Patient-Centered Care occurred in Santiago de Chile. Four keynotes, two roundtables, five workshops, 31 oral and 19 poster presentations from both research and clinical practice took place during the two conference days with 196 participants on location. Conclusion: Establishing the PCC NET has facilitated international collaboration, knowledge exchange, and capacity-building for PCC implementation in Chile. Through different communication strategies, such as workshops, seminars and a conference, it was possible to enhance awareness and practical knowledge among healthcare pro-fessionals and policymakers. These initiatives represent significant steps toward ad-vancing PCC in Chile, although continued efforts are needed to address remaining challenges and sustain momentum in policy and practice.